Cryptocentrum beckendorfii (Orchidaceae: Maxillariinae), an extraordinary new species from Andean Peru - Carnevali, German; Cetzal-Ix, William; Whitten, W. Mark (Phytotaxa, 2012)
Cryptocentrum beckendorfii is described and illustrated from a single cultivated plant reputedly from the Amazonian slopes in the Cuzco region of Andean Peru. This species is similar to C. pseudobulbosum, also from the Amazonian slopes of the Andes, with which it shares sympodial habit with pseudobulbs unlike most species of the genus, which are monopodial and lack pseudobulbs. It differs from C. pseudobulbosum in its larger pseudobulbs, which are totally naked upon maturity, thinly coriaceous, conduplicate foliar blades, sheaths enveloping the pseudobulbs lacking foliar blades and the much longer inflorescences with thin peduncles, among other characters. The putative phylogenetic position of this species is discussed. An identification key and a map of the species of Cryptocentrum present in Peru are provided. The conservation category of the species according to IUCN criteria was assessed as data deficient (D).